The The Impact of Basic Life Support Training for Healthcare Workers in Primary Care on Emergency Patient Outcomes - Muhammad Ishaq Porkas Lubis (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Basic Life Support (BLS) is a crucial emergency intervention that significantly improves survival rates in patients experiencing cardiac arrest or other life-threatening conditions. Primary healthcare facilities often serve as the first point of contact for emergency cases, making it essential for healthcare workers to possess adequate BLS skills. However, variations in training frequency and experience affect the proficiency of healthcare workers in performing BLS effectively. This study aims to analyze the impact of BLS training for healthcare workers in primary care settings on patient outcomes in emergency situations. A literature review and data analysis were conducted to assess the correlation between BLS training and patient outcomes, focusing on survival rates, response time, and procedural effectiveness. Data were collected from various studies, training programs, and case reports related to emergency response in primary healthcare settings. The findings indicate that healthcare workers who receive regular and structured BLS training demonstrate improved knowledge, faster response times, and higher success rates in emergency interventions. Patients treated by trained healthcare workers have better survival rates and reduced complications compared to those treated by untrained personnel. Additionally, the frequency of refresher courses and hands-on simulation training play a significant role in maintaining BLS competency.BLS training for healthcare workers in primary care settings significantly enhances emergency response efficiency and improves patient outcomes. Regular and systematic training programs should be implemented to ensure that healthcare professionals remain proficient in life-saving techniques. This study highlights the need for policy improvements in BLS education to optimize emergency medical care at the primary healthcare level.